Hepatocellular carcinoma: cost-effectiveness of screening. A systematic review - Ruggeri M (Dove Medical Press, 2012)
Matteo RuggeriFacoltà di Economia, Università Cattolica del Sacro Cuore – sede di Roma, Rome, ItalyAbstract: Hepatocellular carcinoma (HCC) is one of the most common tumors worldwide. HCC is a potential target for cancer surveillance (or screening) as it occurs in well-defined, at-risk populations. Curative therapy is possible only for small tumors and screening strategy has been recommended by the US, Italian, and other international liver societies and is practiced widely, but its benefits are not clearly established. The objective of this study was to review the available evidence with respect to the cost-effectiveness of key technologies in the prevention HCC. The literature search was conducted with the support of PubMed. Firstly we selected articles by reading the abstracts. Secondly, we read the articles and the revision was further restricted, with the following as inclusion criteria: (1) full economic evaluation of HCC screening programs; (2) comparison between HCC techniques; (3) outcome measures expressed in terms of quality adjusted life years (QALY); (4) full text availability. The initial review of the literature yielded 346 articles. Of those, 288 were excluded at the first stage. Of those excluded, 108 did not meet the target, 106 did not present the cost analysis, 33 did not analyze the treatment of the disease, and in 41 the abstract was not available. Of the 58 included in the first step, seven examined the cost-effectiveness of different HCC screening techniques, seven investigated the cost-effectiveness of HCC screening versus no screening, and one looked at the cost-effectiveness of timing for HCC surveillance and monitoring, while 43 were about HBV vaccination and screening. We included only the seven articles examining the cost-effectiveness of different HCC screening techniques. In general, incidence is the key parameter which determines the cost-effectiveness of HCC screening. Discrepancies in the results exist when determining the type of technology to be used. Ultrasound (US) alone or in association with alpha fetoprotein (AFP) technology is likely to be the most cost effective and the use of computed tomography (CT) gives controversial results.Keywords: HCC screening, economic evaluations, systematic review